1991
DOI: 10.1002/jsfa.2740540207
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin contamination in mustard (Brassica juncea) in relation to agronomic practices

Abstract: Ajlatoxin contamination in two varieties of mustard (Brassica juncea L), Varuna and BR-40, sown on three planting dates (1, 15 and 30 November) under two different cropping patterns, uiz monocropping and mixed cropping (along with the UP-262 variety of wheat), was examined in rabi (winter) crops of 1987-1988 and 1988-1989. Analysis of variance showed a significant effect of planting date and cropping pattern as well as a combined effect of planting date x cropping pattern. Delayed planting (30 November) result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, the greater susceptibility of M, to A j u i w facilitated more aflatoxin production when inoculated. The role of genetic variability in AJuzus infection and aflatoxin production has been determined for several crops including maize (Lillehoj and Zuber 198 I), mustard (Bilgrami et a/ 1991) and groundnut (Mehan and McDonald 1983). Furthermore, the shorter maturity period of the variety Diara composite (80 days) may minimise aflatoxin contamination by reducing the time span of exposure to fungal propagules under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the greater susceptibility of M, to A j u i w facilitated more aflatoxin production when inoculated. The role of genetic variability in AJuzus infection and aflatoxin production has been determined for several crops including maize (Lillehoj and Zuber 198 I), mustard (Bilgrami et a/ 1991) and groundnut (Mehan and McDonald 1983). Furthermore, the shorter maturity period of the variety Diara composite (80 days) may minimise aflatoxin contamination by reducing the time span of exposure to fungal propagules under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Bilgrami et al, (1991) found mustard seeds of preharvested crops to be contaminated with various levels of aflatoxin. Delayed planting resulted in a high incidence of aflatoxin.…”
Section: Other Spices and Herbsmentioning
confidence: 99%
“…Mustard is a susceptible substrate for aflatoxin contamination (Sahay and Prasad, 1990;Bilgrami et al, 1991). Bilgrami et al, (1991) found mustard seeds of preharvested crops to be contaminated with various levels of aflatoxin.…”
Section: Other Spices and Herbsmentioning
confidence: 99%
“…are contaminated by moulds and mycotoxins (6)(7)(8) . Aflatoxin synthesized by Aspergillus flavus, A. parasiticus and A. nominus (9) is most potent human carcinogen, classified as Class I carcinogen (IARC 2002). It is also mutagenic, teratogenic and immunosuppressive.…”
Section: Introductionmentioning
confidence: 99%